Making It Matter: Hagiology in a 21st-Century Classroom - Hoel, Nikolas O. (Religions, 2024)
In the early twenty-first century, the humanities are facing attacks on their value. At the same time, colleges and universities in the United States are pressured to retain students as funding models have shifted and become more dependent on tuition dollars, at least in public institutions of higher education. The two go hand in hand because, in this environment, faculty members need to justify what they teach as being relevant to their students, and research has shown that students are more likely to thrive and strive when they see themselves in the curriculum. This is particularly true at Hispanic-Serving and Minority-Serving Institutions. This essay is based on the following question: how do we help students recognize that hagiological texts are relevant to them in a modern world in order to meet both aims? It provides the Life of Anskar as a case study to show that when hagiology is read and analyzed in the classroom in accordance with principles of culturally relevant pedagogy, through comparison and the co-creation of knowledge, the texts provide a way for students to better understand themselves, their world, and the possibility for social justice; in other words, they, the students, matter.